2006
DOI: 10.1021/jm061002i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimalarial Activity of Side Chain Modified 4-Aminoquinoline Derivatives

Abstract: A new series of side-chain modified 4-aminoquinolines have been synthesized and found active against P. falciparum in vitro and P. yoelli in vivo. Compounds 6, 11, 12, and 19 exhibited superior in vitro activity compared to chloroquine. Selected compounds 6, 12, and 19 exhibited significant suppression in the in vivo assay. These analogs form a complex with hematin and inhibit the beta-hematin formation, suggesting that this class of compounds act on a heme polymerization target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(92 citation statements)
references
References 27 publications
4
87
0
1
Order By: Relevance
“…We have demonstrated that 4-aminoquinoline-derived guanidine and tetramethylguanidine analogues ( Figure 1A) with altered chain length exhibit promising activity against CQ-sensitive 7 . Earlier we have also demonstrated that modification on 4-aminoquinoline lateral side chain with thiazolidine-4-one ring substitution ( Figure 1B) has led to compounds with improved antimalarial activity, and some of these compounds were indeed more effective than CQ 14 . Furthermore, lysine and ornithine conjugates were prepared by selectively modifying the pendant amino group of 4-aminoquinoline terminal side chain with amide bond ( Figure 1C).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…We have demonstrated that 4-aminoquinoline-derived guanidine and tetramethylguanidine analogues ( Figure 1A) with altered chain length exhibit promising activity against CQ-sensitive 7 . Earlier we have also demonstrated that modification on 4-aminoquinoline lateral side chain with thiazolidine-4-one ring substitution ( Figure 1B) has led to compounds with improved antimalarial activity, and some of these compounds were indeed more effective than CQ 14 . Furthermore, lysine and ornithine conjugates were prepared by selectively modifying the pendant amino group of 4-aminoquinoline terminal side chain with amide bond ( Figure 1C).…”
Section: Introductionmentioning
confidence: 56%
“…The drug-haematin interactions inhibit the formation haemozoin crystals and the accumulation of significant concentrations of haematin which is toxic to parasite and it is believed to be responsible for killing the parasite [9][10][11][12] . In our efforts to develop effective antimalarial agents, earlier we have reported design, synthesis and antimalarial activity of several side chain-modified 4-aminoquinolines [13][14][15][16] . We have demonstrated that 4-aminoquinoline-derived guanidine and tetramethylguanidine analogues ( Figure 1A) with altered chain length exhibit promising activity against CQ-sensitive 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A high degree of biological activity, e.g. antimalarial, antibacterial, anticancer and antioxidant, have been attributed to these structures and has found application in the pharmaceutical industry [1][2][3][4][5][6]. Their unique spectral and photochemical properties have also found application in a variety of elds such as photolytic cleavage of DNA, electrogenerated chemiluminescence and light emitting diodes [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Quinolines and their derivatives are important heterocyclic compounds because of their wide-ranging biological activities [52][53][54] and interesting photochemical properties [55]. For example, chloroquine (46) has been used for its antimalarial activity for more than 60 years; [56][57][58] bedaquiline (47), an inhibitor of the mycobacterial ATP synthase, has been approved to treat multi-drug resistant tuberculosis, [59] and cabozantinib (48), a multitargeted receptor tyrosine kinase inhibitor, showed effective anticancer activity and has been marketed for the treatment of medullary thyroid cancer ( Figure 4) Quinolines and their derivatives are important heterocyclic compounds because of their wide-ranging biological activities [52][53][54] and interesting photochemical properties [55].…”
Section: Quinolinesmentioning
confidence: 99%
“…For example, chloroquine (46) has been used for its antimalarial activity for more than 60 years; [56][57][58] bedaquiline (47), an inhibitor of the mycobacterial ATP synthase, has been approved to treat multi-drug resistant tuberculosis, [59] and cabozantinib (48), a multitargeted receptor tyrosine kinase inhibitor, showed effective anticancer activity and has been marketed for the treatment of medullary thyroid cancer ( Figure 4) Quinolines and their derivatives are important heterocyclic compounds because of their wide-ranging biological activities [52][53][54] and interesting photochemical properties [55]. For example, chloroquine (46) has been used for its antimalarial activity for more than 60 years; [56][57][58] bedaquiline (47), an inhibitor of the mycobacterial ATP synthase, has been approved to treat multi-drug resistant tuberculosis, [59] and cabozantinib (48), a multitargeted receptor tyrosine kinase inhibitor, showed effective anticancer activity and has been marketed for the treatment of medullary thyroid cancer ( Figure 4) [60].…”
Section: Quinolinesmentioning
confidence: 99%